Notes on aphid parasitoids of Porto Santo Island, Madeira Archipelago (Hymenoptera, Aphidiidae) - Cecilio, A.=700 1 Pita, M.T.; Ilharco, F.A.
(Es, En)
ilus., 9 ref.
Keywords: PARASITOIDES; APHIDOIDEA; HYMENOPTERA; APHIDIDAE; PORTUGAL; PARASITOIDES DE LOS AFIDOS